Alphonse Mucha ([SL] Mucha Foundation, 1998)
A thirty minute documentary film about the life and work of Alphonse Mucha. The film captures Mucha's childhood and youth in Ivancise in Moravia and his studen days in Munich. It follows his travels to Paris, where overnight fame awaited him from Paris to America and finally his return to the land of his birth. The film explores both the creative development of this great artist and the fateful key moments which determined his life-- container.
DVD.
Keywords: Mucha, Alphonse, 1860-1939.